1994
DOI: 10.1001/archinte.1994.00420180022003
|View full text |Cite
|
Sign up to set email alerts
|

Is Misoprostol Cost-effective in the Prevention of Nonsteroidal Anti-inflammatory Drug—Induced Gastropathy in Patients With Chronic Arthritis?

Abstract: MAXAIR™ AUTOHAIiR™(pirbuterol acetate inhalation aerosol) Bronchodilator Aerosol For Inhalation Only BRIEF SUMMARY INDICAT10NS AND USAGE: MAXAIR AUTOHALER is indicated ior the prevention and reversal of bronchospasm in patients wilh reversible bronchospasm including asthma. It may be used with or without concurrent theophylline and/or Steroid therapy. CONTRAINDICATIONS: MAXAIR is contraindicated in patients with a history of hypersensitivity to any of its ingredients. WARNINGS: As with other beta adrenergic ae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1995
1995
2001
2001

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(10 citation statements)
references
References 23 publications
(68 reference statements)
0
10
0
Order By: Relevance
“…[16] The risk reduction of 0.38 percentage units over 6 months is much lower than the risk reduction assumed by Edelson and Tosteson (2.3 percentage units for a 3-month period). [14) Even in patients with rheumatoid arthritis and a history of peptic ulcer, the risk reduction was only 2 percentage units (i.e.…”
Section: Assumptions About the Reduction In Gi Eventsmentioning
confidence: 76%
See 2 more Smart Citations
“…[16] The risk reduction of 0.38 percentage units over 6 months is much lower than the risk reduction assumed by Edelson and Tosteson (2.3 percentage units for a 3-month period). [14) Even in patients with rheumatoid arthritis and a history of peptic ulcer, the risk reduction was only 2 percentage units (i.e.…”
Section: Assumptions About the Reduction In Gi Eventsmentioning
confidence: 76%
“…Economic evaluations of misoprostol prophylaxis for nonsteroidal anti-inflammatory drug-induced gastric ulcer in patients with arthritic conditions (reproduced from Stucki et al, [16] controversial whether the savings from preventing the adverse effects of NSAIDs exceed the cost of using misoprostol. [5,[11][12][13][14][15][16][17][18][19] It is also debated whether the gain in quality of life from avoidance of rare NSAID-induced gastrointestinal complications exceeds the disutility from misoprostol use and the diarrhoea which it may cause. [5,6) If misoprostol prophylaxis is to lead to net costs and a net gain in quality of life, it needs to be determined whether the benefits exceed the costS.…”
Section: The Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…31 The previously conducted reviews on this subject only searched Medline,7 8 or the database in which the economic evaluations were found was not mentioned 910 The number of economic evaluations included in these reviews ranged from five to eight, whereas we identified 10 economic evaluations.…”
Section: Discussionmentioning
confidence: 99%
“…92 Four of the analyses retrieved concerned use of misoprostol by patients with osteoarthritis [93][94][95][96] and one concerned use by patients with rheumatoid arthritis. 97 A crossnational comparison study was also retrieved.…”
Section: Modelling the Cost-effectiveness Of Misoprostol Prophylaxismentioning
confidence: 99%